Pemasaran Destinasi Pariwisata Bagi Dinas Pariwisata Kabupaten Kotawaringin Barat Kalimantan Tengah - Haniek Listyorini; Sri Yuwanti; Renny Aprilliyani; Henry Yuliamnir; Mokhamad Kholil Aswan (Jurnal Pengabdian Masyarakat Waradin, 2022)
Tourism has become a Leading Sector for the Government. The success of tourism destinations in the current era of society 4.0 cannot be separated from the regional ability to develop information systems and promotions based on digital 4.0. The purpose of this activity is to help the Tourism Office's human resources have the basics of destination marketing and open the paradigm of thinking of the Tourism Office's human resources about the importance of marketing. The method is the lecture method, FGD, and direct practice in the field. The Participants of this activity were 7 people who came from Bimtek, namely the West Kotawaringin Regency Tourism Office. This community service activity was carried out on Saturday and Sunday, 16-17 November 2019. The place for this activity took a place at the College of Tourism Economics in Semarang and the Bandungan area. The result of this dedication is the formation of lecture material which includes the Definition of Tourist Attractions, the Definition of Tourism Destinations, and the Uniqueness of Kalimantan's Tourist Attractions which are worth VRIN.